Abhishek009 wrote:
jsphcal wrote:
Which of the following is equal to the average (arithmetic mean) of (x+2)^2 and (x-2)^2?
A. x^2
B. x^2+2
C. x^2 +4
D. x^2+2x
E. x^2+4x
AM of (x+2)^2 +(x-2)^2
= \(\frac{( x^2 + 4x + 4 ) + ( x^2 - 4x + 4 )}{2}\)
= \(\frac{2x^2 + 8}{2}\)
= \(x^2 + 4\)
Hence, answer will be (C) \(x^2 + 4\)please I found answer B. because I factorized the expression (x+2)^2 = (x+2)(x-2) instead of (x+2)^2=(x-2)(x-2)
I used the algeabric formula of (a-b)^2=(a-b)(a+b) so my question is, how do I recognize when an expression of (a-b)^2 is equals to (a-b)(a+b) ?
Thank you in advance